2020
DOI: 10.3390/ijms21239286
|View full text |Cite
|
Sign up to set email alerts
|

Skin Resident γδ T Cell Function and Regulation in Wound Repair

Abstract: The skin is a critical barrier that protects against damage and infection. Within the epidermis and dermis reside γδ T cells that play a variety of key roles in wound healing and tissue homeostasis. Skin-resident γδ T cells require T cell receptor (TCR) ligation, costimulation, and cytokine reception to mediate keratinocyte activity and inflammatory responses at the wound site for proper wound repair. While both epidermal and dermal γδ T cells regulate inflammatory responses in wound healing, the timing and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 125 publications
(248 reference statements)
0
34
0
2
Order By: Relevance
“…Recently, lymphocytes have been highlighted as important cells that regulate wound healing responses. 6 8 We demonstrated a role for lymphocytes, specifically CD4 + lymphocytes, in regulation of dermal fibrosis in the severe combined immune deficient (SCID) mouse model. 9 Of the CD4 + subtypes, two immunoregulatory subsets stand out as producers of IL-10, CD4 + Foxp3 + regulatory T cells (Treg) which also produce transforming growth factor (TGF)-β and CD4 + Foxp3 - CD49b + Lag3 + type 1 regulatory T cells (Tr1) which additionally produce TGF-β, IFN-γ, and low levels of IL-4.…”
mentioning
confidence: 99%
“…Recently, lymphocytes have been highlighted as important cells that regulate wound healing responses. 6 8 We demonstrated a role for lymphocytes, specifically CD4 + lymphocytes, in regulation of dermal fibrosis in the severe combined immune deficient (SCID) mouse model. 9 Of the CD4 + subtypes, two immunoregulatory subsets stand out as producers of IL-10, CD4 + Foxp3 + regulatory T cells (Treg) which also produce transforming growth factor (TGF)-β and CD4 + Foxp3 - CD49b + Lag3 + type 1 regulatory T cells (Tr1) which additionally produce TGF-β, IFN-γ, and low levels of IL-4.…”
mentioning
confidence: 99%
“…The situation is made more complicated by the existence of unconventional γδ T cells, which are very abundant in skin [80]. The lack of skin γδ T cells is associated with late wound resolution and decreased inflammation [81]. Thus, the exact role of T cells in acute wound healing remains complex.…”
Section: Adaptive Immunity In Acute Wound Healingmentioning
confidence: 99%
“…Besides conventional alpha beta T cells, γδ T cells take part in inflammatory response during wound healing. Specifically, they recognize DAMPs and secrete IL-17 and IL-22, which further promote inflammation [81].…”
Section: Adaptive Immunity In Acute Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work conducted in mice indicates the synergistic involvement of IL-1α and IL-7, secreted by keratinocytes, in the expansion of epidermal γδ T cells ( 177 ). γδ T cells are resident epidermal cells, which upon activation secrete KGF and induce the proliferation of epidermal stem cells ( 178 , 179 ). Moreover, it has been shown that in mice IL-1β is indispensable in the recall of inflammatory memory of epidermal stem cells, facilitating wound healing following repeated insults ( 180 ).…”
Section: Il-1 Family Cytokines In the Promotion Of Wound Healingmentioning
confidence: 99%